Hydrogen-Induced Microstructure Changes in Zr/Nb Nanoscale Multilayer Structures; Metals; Vol. 14, iss. 4 - Laptev R. S. Roman Sergeevich; Stepanova E. N. Ekaterina Nikolaevna; Lomygin A. D. Anton Dmitrievich; Krotkevich D. G. Dmitry Georgievich; Sidorin A. A. Aleksey Anatoljevich; Orlov O. S. Oleg Sergeevich (2024, 2024)
Title screen